MtrA Response Regulator Controls Cell Division and Cell Wall Metabolism and Affects Susceptibility of Mycobacteria to the First Line Antituberculosis Drugs - Gorla, Purushotham; Plocinska, Renata; Sarva, Krishna; Satsangi, Akash T.; Pandeeti, Emmanuel; Donnelly, Robert; Dziadek, Jaroslaw; Rajagopalan, Malini; Madiraju, Murty V. (Frontiers in Microbiology, 2018)
The biological processes regulated by the essential response regulator MtrA and the growth conditions promoting its activation in Mycobacterium tuberculosis, a slow grower and pathogen, are largely unknown. Here, using a gain-of-function mutant, MtrAY102C, which functions in the absence of the cognate MtrB sensor kinase, we show that the MtrA regulon includes several genes involved in the processes of cell division and cell wall metabolism. The expression of selected MtrA targets and intracellular MtrA levels were compromised under replication arrest induced by genetic manipulation and under stress conditions caused by toxic radicals. The loss of the mtrA gene in M. smegmatis, a rapid grower and non-pathogen, produced filamentous cells with branches and bulges, indicating defects in cell division and cell shape. The ΔmtrA mutant was sensitized to rifampicin and vancomycin and became more resistant to isoniazid, the first line antituberculosis drug. Our data are consistent with the proposal that MtrA controls the optimal cell division, cell wall integrity, and susceptibility to some antimycobacterial drugs.